Quantitation of Adsorption of Rhizobia in Low Numbers to Small Legume Roots - Anollés, Gustavo Caetano (1986)
Bacteria adsorbed in low numbers to alfalfa or clover root surfaces were counted after incubation of seedlings in mineral solution with very dilute inocula (less than 10(5) bacteria per ml) of an antibiotic-resistant strain under defined conditions. After specified washing, bacteria which remained adsorbed to roots were selectively quantitated by culturing the roots embedded in yeast extract-mannitol-antibiotic agar and counting the microcolonies along the root surface; the range was from about 1 bacterium per root (estimated as the most probable number) to 50 bacteria per cm of root length (by direct counting). This simple procedure can be used with any pair of small-rooted plant and antibiotic-resistant bacterium, requires bacterial concentrations comparable to those frequently found in soils, and yields macroscopic localization and distribution data for adsorbed bacteria over the root surface. The number of adsorbed bacteria was proportional to the size of the inoculum. One of every four Rhizobium meliloti cells adsorbed in very low numbers to alfalfa roots resulted in the formation of a nodule. Overall adsorption of various symbiotic and nonsymbiotic bacterial strains to alfalfa and clover roots did not reflect the specificities of these legumes for their respective microsymbionts, R. meliloti and R. trifolii.